Vision and imagination in Jewish mystical texts - Bagraim, Abigail Sarah (Department of Religious Studies, 2025)
The object of this essay is to critically analyse the historically accepted view of scholars and historians that Judaism is an auditory tradition and to affirm and verify a more modern view that a visual tradition has always existed within Judaism. The focus will be on two main types of the visual phenomenon. Firstly, representational images will be discussed, basing the argument on the rich artistic heritage of the Jewish people. Secondly, various otherworldly visions will be examined, with special reference to visions of the soul whilst in and out of the body. The soul while still in the body is able to have extraordinary visions. These spiritual visions are visible through the faculty of the imagination. They take many forms, including visions of the kavod (glory of G-d) and various other prophetic visions. When the soul actually leaves the body these other-worldly visions of the journeys to heaven and hell give us a glimpse into strange and wonderful realms. The debate will commence with a discussion of the views of the historical writers and of their justification for refusing to recognise the existence of a visual tradition within Judaism on the austere basis that to do so would offend against the prohibition of the Second Commandment not to create images of G-d. The Israelites were set in their historical context with many close neighbours who embraced what they considered to be heathen and idolatrous practices. Because of this they had to become discerning with regard to the upholding of their laws and customs and this led to the development within Judaism of manifold laws and regulations against idol worship. This attitude seemed to spread as a continual thread running throughout Jewish history and the subject of Jewish representational images continues to be a controversial issue. It is as a result of the ban that was sometimes placed on Jewish representational art that the refusal to accept a vibrant Jewish visual tradition has persisted.